Polyamines and regulation of ornithine biosynthesis in Escherichia coli. - Cataldi, A A (1989)
The growth rate of several polyamine-deficient mutants of Escherichia coli was very low in minimal medium and increased markedly upon the addition of putrescine, spermidine, arginine, citrulline, or argininosuccinic acid. The endogenous content of polyamines was not significantly altered by the supplementation of polyamine-starved cultures with arginine or its precursors. In contrast, these compounds as well as putrescine or spermidine caused a 40-fold reduction in intracellular ornithine levels when added to polyamine-depleted bacteria. In vivo experiments with radioactive glutamic acid as a precursor and in vitro assays of the related enzymes showed that the decrease in ornithine levels was due to the inhibition of its biosynthesis rather than to an increase in its conversion to citrulline or delta 1-pyrroline-5-carboxylic acid and proline. High endogenous concentrations of ornithine were toxic for the E. coli strains tested. The described results indicate that the stimulatory effect of putrescine and spermidine on the growth of certain polyamine-starved bacteria may be partially due to the control of ornithine biosynthesis by polyamines.